Commentary: The Role of the Toxicologic Pathologist in Academia. (January 2015) - Turner, P. V.; Haschek, W. M.; Bolon, B.; Diegel, K.; Hayes, M. A.; McEwen, B.; Sargeant, A. M.; Scudamore, C. L.; Stalker, M.; von Beust, B.; Wancket, L. M.
Veterinary pathologists working as toxicologic pathologists in academic settings fill many vital roles, such as diagnosticians, educators, and/or researchers. These individuals have spent years investigating pathology problems that mainly or exclusively focus on the reactions of cells, organs, or systems to toxic materials. Thus, academic toxicologic pathologists are uniquely suited both to help trainees understand toxicity as a cause of pathology responses and also to provide expert consultation on toxicologic pathology. Most toxicologic pathologists in academia are employed at colleges of medicine or veterinary medicine, even though specific toxicologic pathology faculty appointments are uncommon in Europe and North America. Academic toxicologic pathologists typically receive lower financial compensation than do toxicologic pathologists in industry, but academic positions generally provide alternative rewards, such as higher workplace autonomy and scheduling flexibility, professional enrichment through student interactions, and enhanced opportunities for collaborative research and advanced diagnostic investigations. Regular participation by academic toxicologic pathologists in professional training opportunities (eg, as pathology and toxicology instructors in medical and veterinary medical courses, graduate programs, and residencies) offers an important means of engendering interest and inspiring veterinarians to select toxicologic pathology and toxicology as their own areas of future expertise.